Performance of the Modified Mini-Mental State Examination (3MS) in Assessing Specific Cognitive Function in Patients Undergoing Peritoneal Dialysis - Li, Yi (PLoS One, 2016)
PURPOSE: While Cognitive impairment (CI) has been identified as an independent risk factors for mortality in patients undergoing peritoneal dialysis (PD), it is inadequately assessed. We evaluated the applicability of the Modified Mini-Mental State Examination (3MS) in assessing specific cognitive function and compared it to a detailed neuropsychological test battery as the reference standard. METHODS: In this multicentric cross-sectional study, we enrolled 445 clinically stable patients from five PD units, who were undergoing PD for at least 3 months. The 3MS was evaluated for general cognitive function. A detailed neuropsychological battery including domains of immediate memory, delayed memory, executive function, language, and visuospatial ability were evaluated as reference standards. Sensitivity and specificity of the 3MS was determined by using receiver operating characteristic (ROC) analysis. RESULTS: The CI prevalence evaluated by 3MS was 23.6%. PD patients with CI performed worse in all cognitive domains. The 3MS correlated well with specific cognitive domains. However, 18.5%, 57.4%, 12.6%, 8.8%, and 41.2% of patients whom were idendified as normal by 3MS still showed executive dysfunction, immediate memory impairment, delayed memory impairment, and language-ability and visuospatial-ability impairment, respectively. The 3MS identified patients having specific cognitive dysfunction with varied extent of diagnostic value, with 0.50, 0.42, 0.35, 0.34, and 0.26 of Youden index in executive function, delayed memory, language ability, immediate memory, and visuospatial ability, respectively. CONCLUSIONS: The 3MS is not a comprehensive instrument for major cognitive domains in PD patients. It could, however, be used for executive dysfunction and delayed memory impairment screening.